Using Observation Realia to Improve EFL Students’ Writing Ability in Writing English Descriptive Text - Dini Kurnia Irmawati (Program Pendidikan Vokasi Universitas Brawijaya, 2013)
In the teaching of writing, interesting media and appropriate teaching techniques are essential to help learners improve their writing ability. In relation to descriptive text, imagining someone or using pictures to describe has not given meaningful experience for students to get ideas on what to describe and how to describe well. Regarding this, many EFL students of D3 English program of Vocational Program at Brawijaya University still found it difficult to develop and organize ideas of someone’s description. Therefore, using observation realia was proposed to be used as a medium to help students solve their problems in writing a descriptive text. This Classroom Action Research on the use of observation realia was done through process-genre based approach which consisted of 4 stages: planning, implementing, observing and reflecting. The result shows that the use of observation realia through process-genre based approach could improve the students’ writing ability in terms of content, organization and language use. English teachers or lecturers are suggested to use observation realia as one of interesting alternative media in teaching writing. Also, further researchers are suggested to develop the use of observation realia for students with different level of education and for different kinds of text types.